The Concept Of “Huma Betang” As A Model Of Dialogual Faith In The View Of Aloysius Pieris - manek, Anjelinusloi (Universitas Katolik Parahyangan, 2023)
This article delves into the philosophical-theological significance of Huma Betang, the traditional house of the Dayak people in Central Kalimantan, within the context of the Church's faith dialogue. Huma Betang, serving as a cultural representation, articulates values of humanity, familial bonds, communal living, and equality. The research aims to delineate the theological values manifested in the daily dynamics of Huma Betang, concentrating on the faith dialogue within the Church's responsibilities, including diakonia, kerygma, martyria, the celebration of faith/liturgy, and koinonia. The research methodology employs a literature review approach, drawing from previous writings, the perspectives of Aloysius Pieris, and documents from the Catholic Church. The study's findings reveal that the Theology of Huma Betang mirrors the religiosity of Asia, illustrating communal living where the community gathers to listen to the word of God. Values of familial bonds, communal living, and equality serve as the foundation for the everyday dynamics of Huma Betang, illustrating the principle of collective living in harmony with others.